Social protection in Europe 1997. (Employment and social affairs, 1998)
This third report of the European Commission on social protection examines the changes to the scale, pattern, growth and funding of social expenditure. It describes how social expenditure remains one of the major weapons in the fight against poverty and exclusion even while social protection systems are adapted better to fit the needs of the modern labour market.